Analysis of Birth Certificate Issuance Services at the Medan City Population and Civil Registration Service - Fahmi Rizky; Nurbaiti Nurbaiti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
A Civil Registry document which explains the child's name, gender, parents' names, and citizenship status recorded as a result of a birth is called a Birth Certificate. During the Covid-19 pandemic, the Medan City Population and Civil Registry Office created media to facilitate birth certificate issuance services, which were supported by the increasing development of technology and information. The purpose of this study was to find out the birth certificate issuance services carried out by the Department of Population and Civil Registration in Medan City using descriptive qualitative methods which were made into narrative form with data collection techniques through direct observation and interviews with the community. The results obtained from this study indicate that the process carried out to make a Birth Certificate is sufficient in accordance with the SOP. The online SIBISA service simplifies and speeds up the administrative process for issuing birth certificates during the pandemic..